PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERCOBAAN ATAU PERMUFAKATAN JAHAT UNTUK MELAKUKAN TINDAK PIDANA NARKOTIKA (studi putusan nomor. 17/pid.sus/2019/Gns) - zainab ompu jainah; Anggalana Anggalana; Rachmad Kurniawan (Jurnal Pro Justitia (JPJ), 2022)
Based on Decision Number. 17 / Pid.Sus / 2019 / PN Gns stated that Defendant I. Supriyatno Bin Sumardi, Defendant II. Adi Wibowo Bin Kusnudin, Defendant III. Suryo Dandoko Als Koko Bin Suro and Defendant IV. Rahmad Als Towong Sanusi was legally and convincingly proven guilty of committing a criminal act of jointly abusing narcotics class I for himself. The research method used normative and empirical juridical approaches. Sources of normative and empirical data. Collecting data through library research and field research. The data analysis used was qualitative juridical. The results of the research and discussion show that the factors causing the occurrence of criminal acts of trial or conspiracy to commit narcotics crime based on Decision Number: 17 / Pid.Sus / 2019 / PN Gns are due to economic factors, family environmental factors, social environmental factors and lack of understanding and appreciation and practice of religious values. The application of criminal sanctions against perpetrators of criminal trials or conspiracy to commit criminal acts of narcotics based on Decision Number: 17 / Pid.Sus / 2019 / PN Gns is to impose crimes against Defendant I. Supriyatno Bin Sumardi, Defendant II Adi Wibowo Bin Kusnudin, Defendant III. Suryo Dandoko Als Koko Bin Suro and Defendant IV. Rahmad Als Towong Sanusi, with imprisonment for 1 (one) year and 10 (ten) months respectively. The factors inhibiting the application of criminal sanctions against the perpetrators of criminal trials or conspiracy to commit the crime of narcotics are the legal factors themselves, community factors and cultural factors.